2004
DOI: 10.1177/0363546503258935
|View full text |Cite
|
Sign up to set email alerts
|

Does the Patellar Tendon Normalize after Harvesting Its Central Third?

Abstract: Prospective MRI examinations revealed that the patellar tendon at the donor site had not normalized 6 years after harvesting its central third. The reharvesting of the patellar tendon can therefore not be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 30 publications
2
40
0
4
Order By: Relevance
“…15,16,21 Other tendinopathic-like features such as mild degenerative changes, 18 increase in cellularity and vascularity, 17 hypoechogeneity, and hyperechogeneity, 15,20,21 increase in tendon width 15,[17][18][19][20]21 as observed with MRI and ultrasonography have also been reported. Bayar et al 15 further described their patients having changes similar to tendinopathy in 6 out of 20 patients.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…15,16,21 Other tendinopathic-like features such as mild degenerative changes, 18 increase in cellularity and vascularity, 17 hypoechogeneity, and hyperechogeneity, 15,20,21 increase in tendon width 15,[17][18][19][20]21 as observed with MRI and ultrasonography have also been reported. Bayar et al 15 further described their patients having changes similar to tendinopathy in 6 out of 20 patients.…”
mentioning
confidence: 91%
“…[8][9][10][11][12] Clinical studies have occasionally reported ectopic calcification after Achilles tendon rupture 13,14 as well as calcification and tendinopathic-like changes in patellar tendon donor site after anterior cruciate ligament (ACL) reconstruction. [15][16][17][18][19][20][21] We hypothesized that chondro-osteogenesis and change in the ECM composition of the repair tissue after acute tendon injury might contribute to the poor tissue quality. This study therefore aimed to examine the presence of chondrocyte phenotype and ossification inside the window wound of the patellar tendon.…”
mentioning
confidence: 99%
“…Em nosso estudo a ativação das plaquetas para formação do gel foi feita utilizando trombina autóloga, obtida do plasma do próprio paciente. (37) , histopatologia (42) e ressonância magnética (35,36,(38)(39)(40)(41)(42) . Consideramos, a partir desses estudos, a ressonância magnética como um método de imagem apropriado para comparar a regeneração do ligamento da patela nos casos em que adicionamos o PRP com um grupo controle, em que nada foi acrescentado.…”
Section: Discussionunclassified
“…Os trabalhos existentes mostram que há a presença de um processo natural de regeneração do ligamento da patela após a retirada de enxerto, sem a adição de PRP ou fatores de crescimento (35,36,(38)(39)(40)(41)(42) . Os estudos com ressonância magnética seriada mostram que aos seis meses de pós-operatório a largura desse defeito, inicialmente de 10 mm, situa-se entre 6 mm (38) e 9 mm (39) , em média.…”
Section: Discussionunclassified
See 1 more Smart Citation